The Concordance between Nonclinical and Phase I Clinical Cardiovascular Assessment from a Cross-Company Data Sharing Initiative. (21st September 2014) - Ewart, Lorna; Aylott, Mike; Deurinck, Mark; Engwall, Mike; Gallacher, David J.; Geys, Helena; Jarvis, Philip; Ju, Haisong; Leishman, Derek; Leong, Louise; McMahon, Nick; Mead, Andy; et al.
Abstract: It is widely accepted that more needs to be done to bring new, safe, and efficacious drugs to the market. Cardiovascular toxicity detected both in early drug discovery as well as in the clinic, is a major contributor to the high failure rate of new molecules. The growth of translational safety offers a promising approach to improve the probability of success for new molecules. Here we describe a cross-company initiative to determine the concordance between the conscious telemetered dog and phase I outcome for 3 cardiovascular parameters. The data indicate that, in the context of the methods applied in this analysis, the ability to detect compounds that affect the corrected QT interval (QTc) was good within the 10–30x exposure range but the predictive or detective value for heart rate and diastolic blood pressure was poor. These findings may highlight opportunities to refine both the animal and the clinical study designs, as well as refocusing the assessment of value of dog cardiovascular assessments beyond phase 1. This investigation has also highlighted key considerations for cross-company data sharing and presents a unique learning opportunity to improve future translational projects.